BACTERIOLOGICAL PATTERNS AND ANTIBIOTIC SENSITIVITIES IN CALCULUS CHOLECYSTITIS - Farooq, Muhammad Omar; Mian, Amer; Saeed, Bilal; Ikram, Amir; Qasmi, Shehzad Ahmed (Journal of Ayub Medical College Abbottabad, 2014)
biliary tract. There is an inherent difficulty in identifying patients having infected gall bladders who may have the risk of wound infection or gram negative septicaemia after cholecystectomy. This study was conducted to ascertain the bacteriological patterns and antibiotic sensitivities of bile in calculus cholecystitis patients presenting at a tertiary care hospital and formulate guidelines for prophylactic antibiotic therapy. Methods: This descriptive study was conducted in Combined Military Hospital, Rawalpindi from 20th Dec 2006 to 19th Sep 2008. A total number of 150 patients presenting at CMH Rawalpindi for elective cholecystectomy were included in the study. Prophylactic antibiotics were given after the induction of anaesthesia, 5 ml of bile was aspirated from their intact gall bladder was subjected to bacteriological examination at Armed Forces Institute of Pathology. A pro forma was designed to record all the information regarding isolated bacteria and their sensitivities to various antibiotics. Data was analyzed using SPSS-11. Results: Growth of bacteria was seen in 57 (38%) cases and no growth was seen in 93 (62%). Most common organism cultured was: Pseudomonas aeruginosa followed by Escherichia coli (E. Coli) and Klebsiella pneumoniae. The most effective antibiotic was Imipenem followed by Piperacillin- Tazobactum combination and Amikacin. Conclusions: Imipenem, Piperacillin-Tazobactum combination and Amikacin should be used for prophylaxis in cases of cholelithiasis undergoing elective cholecystectomy. Keywords: Cholecystectomy, bile culture, cholelithiasis, prophylactic antibiotics